THE STUDY OF TABOO AND EUPHEMISM ON THE ENGLISH DEPARTMENT STUDENTS IN UNIVERSITAS PAMULANG - Haryati Haryati (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2020)
This study was aimed to find out the kinds of taboo and euphemism words among college students of faculty of letter at Universitas Pamulang, and the reasons why the students select to utter taboo or euphemisms. A qualitative analysis including would be conducted in this research. The respondents of this study were the fourth semester students (regular A class) taking the speaking 4 at English department of Pamulang University academic year 2018/2019. Out of 176 students of the population, 40 students (20 males and 20 females) will be chosen as the samples based on the purposive sampling. To collect the data, the writer used two kinds of instruments: an observation of students’ speaking conversation and interview. These instruments were administered to answer stated research questions. As a result, the writer found that most male students preferred uttering taboo words, and the female students seemed to utter euphemism instead of taboo words. The result was influenced by some factors. Theoretically, the research finding would enrich the teachers’ skills to introduce euphemism as a substitution to replace the use of taboo words in students’ conversation and assist students to utter proper words in social situation that leads politeness.